2013
DOI: 10.1007/s10661-013-3189-0
|View full text |Cite
|
Sign up to set email alerts
|

A monitoring of environmental effects from household greywater reuse for garden irrigation

Abstract: The option of reusing greywater is proving to be increasingly attractive to address the water shortage issue in many arid and semiarid countries. Greywater represents a constant resource, since an approximately constant amount of greywater is generated from kitchen, laundries, bathroom in every household daily, independent of the weather. However, the use of greywater for irrigation in particular for household gardening may pose major hazards that have not been studied thoroughly. In this study, a 1-year monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…Therefore, the graywater treated by the filtration system was acceptable for discharge upstream of the drain. In comparison with different natural filtration systems for graywater, Mohamed et al (2013b) studied the efficiency of a natural filtration system consisting of a gravel‐sand pretreatment layer followed by a natural peat layer as the primary filter medium to treat kitchen wastewater by percolation. The study found that the quality of the treated wastewater complied with the limits of Standard B of the Malaysian EQA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the graywater treated by the filtration system was acceptable for discharge upstream of the drain. In comparison with different natural filtration systems for graywater, Mohamed et al (2013b) studied the efficiency of a natural filtration system consisting of a gravel‐sand pretreatment layer followed by a natural peat layer as the primary filter medium to treat kitchen wastewater by percolation. The study found that the quality of the treated wastewater complied with the limits of Standard B of the Malaysian EQA.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the name Parit Raja means “king of drains,” so named because this site contains many drains. The untreated graywater may create an ideal environment especially for pathogenic bacteria to proliferate and provide a breeding environment for insects (Mohamed et al 2013a, 2013b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Hamaiedeh and Bino (2010) indicated that salinity, sodium adsorption ratio and organic content of soil increased as a function of duration of greywater usage at the Al-Amer villages in Jordan. An Australian study showed that salinity, SAR, and the organic content of the soil increased as a function of time and affected the plant growth (Mohamed et al 2013).…”
Section: Soil Sodicitymentioning
confidence: 99%
“…The reported values of sodium were significantly higher than the control samples and this is owing to the use of cleaning products by the refuges inside the camp which contains high level of sodium (Mohamed et al, 2013;Revitt et al, 2011). Furthermore, Gross et al, (2005);Travis, et al, (2010) have reported that high level of sodium will cause soil hydrophobicity and impact the soil structure negatively as well as impact the capacity of the soil to support plant growth.…”
Section: Effects Of Grey Water On Soilmentioning
confidence: 94%